Vitiligo Fokal pada Anak Yang Diterapi dengan Target Excimer Light 308 nm - Stefani Nurhadi (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2019)
Vitiligo is a acquired skin disease characterized by a well-defined depigmented macules caused by progressive loss of functional melanocytes. Vitiligo usually appears first during childhood or young adults. Management of vitiligo in children are more difficult because the preference of therapy is limited when compared with adult. Targeted 308 nm UVB phototherapy is used for local vitiligo in children as it can be focused on the lesion and reduce the side effects. A 4-year-old girl, came to dermato-venereology polyclinic of Indera Hospital Denpasar with complaints of white patch on her lips for 3 weeks. Based on the history and physical examination, she was diagnosed with focal vitiligo. She was treated with targeted 308 nm excimer light phototherapy three times a week. Five sessions of phototeraphy resulted good response characterized by repigmentation of the lesion without redness and blisters.The therapy aims to achieve the best results with minimal side effects. Phototherapy targets are recommended for local vitiligo and especially for new small lesions as well as pediatric vitiligo. The mechanisms of this phototherapy is to trigger repigmentation, stabilization, immunosuppression and immunomodulation. The conclusion is targeted 308 nm phototherapy is quite useful for treating vitiligo even though more therapy sessions are needed.